A Comparison of Surgical Outcome of Major Pancreatic Resections: Left Pancreatectomy Versus Pancreaticoduodenectomy - Ariotti, Riccardo; Pecorelli, Nicolò; Capretti, Giovanni; Carvello, Michele; Gilardini, Cristina; Castoldi, Renato F; Braga, Marco; Staudacher, Carlo; Balzano, Gianpaolo (JOP. Journal of the Pancreas, 2012)
Context Left pancreatectomy (LP) is considered a minor operation, when compared to pancreaticoduodenectomy (PD), due to a technically easier resection, without the burden of pancreatic anastomosis. Nonetheless LP is a demanding procedure with high blood loss and a high rate of postoperative pancreatic fistula. Objective To compare surgical outcome between patients undergoing PD and LP in a high volume institution. Methods Retrospective study on prospectively collected data on 981 consecutive patients undergoing PD (n=664) and LP (n=317), between 2004 and 2011. Postoperative complications were stratified according to Clavien-Dindo classifications (major complications III-V). Pancreatic fistula (PF) was defined according to ISGPF classifications. Results Mortality was higher in PD (3.6% vs. 0.3%, P<0.001), but overall morbidity was the same (63% in both groups). Postoperative major complications were more frequently in PD group (18.4% vs. 5.3%, P<0.001). PF was more frequent in LP (PD 30% vs. LP 46%, P<0.001); however, clinically significant grade B and C PF rate was higher in PD (16% vs. 6%, P<0.001). Intraoperative blood loss was similar between groups (PD 568±388 mL, LP 619±685 mL, P=0.169), however the rate of patients who received a blood transfusion intraoperatively was higher in the PD group (35% vs. 22%, P<0.001). This was probably due to a higher number of patients presenting with preoperative anemia (mean hemoglobin: PD 12.4±2.2 g/dL vs. LP 13.2±1.7 g/dL, P<0.001). PD patients were transfused more postoperatively (20% vs. 11%, P<0.001) and had a higher mean volume of postoperative transfusion (232±811 mL vs. 79±281 mL, P<0.001). Conclusion As expected, mortality and major complications were higher after PD. Overall morbidity and intraoperative blood loss were similar between the two operations.